Efficient nonlinear-optical behaviors of chiral-amide-bonded porphyrin noncovalent functionalized MWCNTs by terminated pyrene units. (20th August 2020) - Zhu, Weihua; Zhang, Honglin; Liu, Siqi; Wang, Aijian; Liang, Xu
Abstract : Four chiral porphyrins and their derivatives with chiral-amide-bonded terminal pyrene were synthesized and isolated. Abstract : Four chiral porphyrins and their derivatives with chiral-amide-bonded terminal pyrene were synthesized and isolated. Structural characterization as well as electronic structure investigations were carried out to understand the effect of bridging an amide-bond on the molecular chirality. It has been clearly demonstrated that the nonlinear optical behaviors could be enhanced by surface orderly arrangement arising from introducing terminal pyrene units resulting in an efficient charge transfer effect from the porphyrins to MWCNTs.